Aberrant hepatic lipid metabolism associated with gut microbiota dysbiosis triggers hepatotoxicity of novel PFOS alternatives in adult zebrafish. (August 2022) - Wang, Qiyu; Huang, Jing; Liu, Shuai; Wang, Caiyun; Jin, Yuanxiang; Lai, Hong; Tu, Wenqing
Graphical abstract: Highlights: The order of hepatotoxicity to adult zebrafish is F-53B > PFOS > OBS. PFOS, F-53B, and OBS alter zebrafish liver histopathology and liver function. PFOS and F-53B lead to aberrant hepatic lipid metabolism by acting on PPARγ. Gut microbiota dysbiosis may contribute to PFAS-induced alterations in the PPAR pathway. Abstract: Perfluorooctane sulfonate (PFOS) has been reported to induce hepatotoxicity in wildlife and humans. Novel PFOS alternatives have been widely used following restrictions on PFOS, but little is known about their potential toxicity. Here, the first comprehensive investigation on the chronic hepatotoxicity and underlying molecular mechanisms of PFOS, 6:2Cl-PFESA (F-53B), and sodium p -perfluorous nonenoxybenzene sulfonate (OBS) was carried out on adult zebrafish through a histopathological examination, biochemical measurement, and multi-omics analysis. PFOS and its alternatives caused changes in liver histopathology and liver function indices in the order of F-53B > PFOS > OBS, which was consistent with their concentration in the liver. In silico modeling and transcriptional profiles suggested that the aberrant hepatic lipid metabolism induced by F-53B and PFOS was initiated by the action on peroxisome proliferator-activated receptor γ (PPARγ), which triggered changes in downstream genes transcription and led to an imbalance between lipid synthesis and expenditure. Gut microbiome analysis provided another novel mechanistic perspective that changes in the abundance of Legionella, Ralstonia, Brevundimonas, Alphaproteobacteria, Plesiomonas, and Hyphomicrobium might link to alterations in the PPAR pathway based on their significant correlation. This study provides insight into the molecular mechanisms of hepatotoxicity induced by PFOS and its novel alternatives and highlights the need for concern about their environmental exposure risks.